Mechanistic and therapeutic insights into the function of different cell death modalities in rheumatoid arthritis: emphasis on the crosstalk with non-coding RNAs - Wen, Jianting; Liu, Jian; Wan, Lei; Wang, Fanfan (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA), a prevalent autoimmune disorder, imposes a substantial burden on global health due to its progressive disability and compromised patient well-being. Although the precise etiology of this condition is still not fully understood, current research implicates intricate interactions between dysregulated immune cells and pro-inflammatory mediators. Recent scientific advancements have highlighted the pathogenic significance of programmed cell death (PCD) mechanisms (including spanning apoptosis, autophagy, ferroptosis, necroptosis, senescence, and pyroptosis) in RA pathophysiology. Emerging evidence has established these cellular demise pathways as critical contributors to synovial inflammation and joint destruction. This comprehensive analysis systematically examined the mechanistic involvement of distinct cell death modalities in RA development, with particular focus on their regulatory interplay with non-coding RNAs (ncRNAs). Furthermore, the emerging therapeutic potential of traditional Chinese medicine (TCM) formulations in modulating these cell death networks was evaluated, ultimately proposing novel translational frameworks for targeted RA intervention.